Financial Ratio Analysis of Sharia Bank in Indonesia - Esty Apridasari (Jurnal Internasional Ekonomi Islam, 2020)
The development of Sharia Banking in Indonesia in the last few years is arguably relatively rapid. This progress is indicated by the increasing number of Islamic financial institutions, Sharia Banks and Sharia Business Units. This study analyzes the financial ratios of Sharia Banks in Indonesia to determine the performance and health of Sharia banks from 2014 to 2018. This study uses secondary data by looking at CAR. BOPO, NPF, FDR and NOM as financial ratios. The results show that the analysis of the financial ratios of Sharia Banks in Indonesia from 2014 to 2018, several ratio values are by the standard set by Bank Indonesia, which are CAR, BOPO, and NPF. As for FDR, in the last two years of the research period, the value was still below the standard set by Bank Indonesia. Likewise, for the NOM ratio, the value is still far below the standard set by Bank Indonesia. This research shows that the financial ratio of Sharia Banks in Indonesia is generally still having a good rating; it means that their performance during the research period year is quite good.